The development of surveillance and rapid response team model at Ban Tham-Hin Temporary Shelter by participatory process, Suan Phueng District, Ratchaburi Province - อารีย์รบ, ปาจรีย์ (Disease Control Journal, 2017)
This research aims to (1) describe the status of epidemiological diseases at Ban Tham-Hin temporary shelters (2) develop the surveillance and rapid response team model by participatory process at the community level and (3) monitor and evaluate the model. The population of this research are divided in three groups (1) the refugees from the fighting of 7,383 people and 15 leaders living in temporary shelter (2) the officers at the shelter and (3) the represent of local Thai people who lived at surrounding area. The research was conducted into three phases following by the objectives above since 1st January 2011 - 31st December 2014. Both of quantitative and qualitative data were used in this research. The analysis of data classified in two ways as following; (1) qualitative data analyzed through observation and participation (participant observation) and (2) the quantitative analyzed data by descriptive statistics such as percentage, mean and standard deviation. The study found that the model of surveillance and rapid response team at Ban Tham-Hin temporary shelter by participatory process Suan Phueng district, Ratchaburi province has five components: (1) coordination center of public health border (2) health data center (3) academic supporting unit (4) key important leaders and (5) rapid response team setting. The results has shown that the refugees had the rate of patients with communicable diseases decreased from 2012 to 2014 by the rate per ten thousand patients of 4,097.92, 4,190.45 and 4,005.15, respectively. Moreover, the refugees’ satisfaction of the development of this model of the entire three years at a high level (X = 2.45, SD = 0.659), (X = 2.51, SD = 0.607) (X = 2.52, SD = 0.692) respectively. Research found that the public relations and promote the access to health information should develop in every levels at the temporary shelter.